The Bloomsbury handbook of prison education - Corbett, Erin S. (Bloomsbury Academic, 2024)
"Written by activists and scholars based in Australia, Kenya, Pakistan, New Zealand, South Africa, Uganda and the USA, The Bloomsbury Handbook of Prison Education offers the first global state-of-the-field overview of research into educational practices and programs in prisons. It covers the history of the field and puts forward future directions for research. The range of topics covered include discussions of how gender, race, sexuality, indigeneity, age and faith impact incarceration rates around the world; educational leadership; STEM education; creative writing programs; distance learning; abolition; education after prison and education for correctional staff. The book includes a Foreword by Donald Sawyer, III, Vice President of Diversity, Inclusion, and Belonging at Fairfield University, USA."--Publisher's website